Comparing the structure and composition of riparian woodlands in three northeast Kansas lake watersheds - Maradiaga Rodriguez, Dalila del Carmen (Kansas State University, 2012)
Riparian forests are more effective than other land cover types at stabilizing stream banks during high water events. Tree trunks and roots can slow flood-waters, thus retaining sediment deposition within riparian areas instead of downstream in reservoirs. This project is part of a larger, multi-agency study on reducing sedimentation of federal reservoirs. Between August 2010 and May 2012, riparian forests were assessed in the watersheds of three northeast Kansas lakes: Atchison County, Banner Creek, and Centralia City. The predominant land use in those watersheds is agricultural, with Atchison and Centralia watersheds dominated by cropland and Banner dominated by grassland. Plot dimensions were 50ft by 30ft (1500 ft[superscript]2) measured from the top of the streambank outward to the extent of the predetermined active channel width (ACW). Forty-four plots were assessed across the three watersheds. Data collected in each plot were used to determine the basal area (BA) in ft[superscript]2 per acre, trees per acre (TPA), tree height by crown class, and quadratic mean diameter (QMD) by species. Results showed some trends in BA and TPA among the three watersheds, however differences were not significant. The average BA of trees in riparian woodlands in the Centralia watershed was 155 ft[superscript]2 (dominated by cottonwood (Populus deltoides) with some honeylocust (Gleditsia triacanthos)); the Atchison and Banner watersheds showed an average BA of 120 ft[superscript]2. The Atchison watershed was dominated by honeylocust and walnut (Juglans nigra) but the Banner watershed was dominated by bur oak (Quercus macrocarpa) and hackberry (Celtis occidentalis). However, the Atchison watershed had the most TPA (194), as well as the tallest trees of the three watersheds. The Atchison watershed had the highest QMD in oak, whereas the Banner and Centralia watersheds had the highest QMD in cottonwood. Banner watershed had more plots with seedlings, whereas Atchison watershed had more plots with saplings. Overall, forest regeneration primarily comprised hackberry seedlings and saplings, with hickory saplings more common in the Banner watershed. For each watershed, the composition and structure of riparian vegetation differed but not significantly.
Keywords: Vegetation; Sedimentation; Regeneration; Forest; Inventory; Agronomy (0285); Forestry (0478); Horticulture (0471)